HUBUNGAN KUALITAS PELAYANAN DENGAN KEPUASAN PASIEN DI KLINIK PRATAMA RAWAT JALAN SEKOLAH POLISI NEGARA (SPN) POLDA JATENG - Prihastuti, Dewi; Susanti, Indri Heri; Khasanah, Suci (SINERGI : Jurnal Riset Ilmiah, 2025)
High-quality healthcare services are crucial for public trust and service utilization. Patient satisfaction serves as a key measure of service quality, encompassing treatment outcomes and overall patient experience. At Klinik Pratama Rawat Jalan SPN Polda Jateng, complaints regarding administrative procedures, long waiting times, and waiting area comfort highlight areas needing improvement. This study analyzed the relationship between service quality and patient satisfaction using a quantitative, cross-sectional design with 84 patients selected through purposive sampling. Validated questionnaires assessed both variables, and data were analyzed using the Spearman correlation test. Results showed that most patients rated service quality as moderate to high and reported being satisfied with services. The Spearman test indicated a significant positive relationship between service quality and patient satisfaction (p < 0.05), confirming that higher service quality leads to greater patient satisfaction. The study recommends clinic management focus on enhancing tangible aspects, responsiveness, and assurance to provide patient-centered, high-quality healthcare services.